Optimization Tools in Management and Finance - Ferreira, M. A. M. (EasyChair Preprint Nº 8346, 2025)
Through this paper, the most used in management and finance optimization problems mathematical tools are presented, in a combined coherent way. The respective mathematical fundaments are synthetically outlined, and the resolution methods are briefly described, hopping that this text functions as a manual in these matters.